Developing netball-specific speed zones for quantifying on-court locomotor demands: Implementation of a mathematical model using Global Positioning Systems (GPS) - Rodgers, Aneesha (Stellenbosch : Stellenbosch University, 2026)
Thesis PhD (Sport Sc)--Stellenbosch University, 2026.